Multi‐focus image fusion via morphological similarity‐based dictionary construction and sparse representation. Issue 2 (1st June 2018) - Qi, Guanqiu; Zhang, Qiong; Zeng, Fancheng; Wang, Jinchuan; Zhu, Zhiqin
Abstract : Sparse representation has been widely applied to multi‐focus image fusion in recent years. As a key step, the construction of an informative dictionary directly decides the performance of sparsity‐based image fusion. To obtain sufficient bases for dictionary learning, different geometric information of source images is extracted and analysed. The classified image bases are used to build corresponding subdictionaries by principle component analysis. All built subdictionaries are merged into one informative dictionary. Based on constructed dictionary, compressive sampling matched pursuit algorithm is used to extract corresponding sparse coefficients for the representation of source images. The obtained sparse coefficients are fused by Max‐L1 fusion rule first, and then inverted to form the final fused image. Multiple comparative experiments demonstrate that the proposed method is competitive with other the state‐of‐the‐art fusion methods.